Are athletes burning out with passion? - Gustafsson, H.; Hassmen, P.; Hassmen, N. (European Journal of Sport Science, 2011)
Passion is a strong motivational force towards an activity considered very important, possibly to the extent that the activity forms a part of an individual's identity. Two forms of passion, harmonious and obsessive, are thought to lead to different cognitive and affective responses. Although being passionate about sport appears to be important from a motivational perspective, it possibly also increases the risk for burnout, which is a negative consequence blamed partly on too much training and inadequate recovery. The question voiced in this study is whether harmonious passion and obsessive passion pose equal risks for burnout. Participants were 94 female and 164 male competitive athletes from 21 sports. The results, analysed using partial correlation and multivariate analyses of variance, showed that athletes with an obsessive passion scored higher on a burnout inventory than did harmoniously passionate athletes. Obsessively passionate athletes also scored higher on perceived stress and negative affect, and lower on positive affect. These findings support the assumption that even though the two forms of passion may be an integral part of elite sports, athletes scoring high on obsessive passion may be at greater risk of developing burnout than more harmoniously passionate athletes. Burning bright and burning out can thus be seen as two potential consequences for athletes driven by passion. Athletes and coaches who are aware of this may be better equipped to avoid the potential negative consequences associated with too much stress and too little recovery.